2022
DOI: 10.3389/fspor.2022.875767
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 Lockdown on Physical Performance, Sleep Quality, and Health-Related Quality of Life in Professional Youth Soccer Players

Abstract: BackgroundIn March 2020, the COVID-19 outbreak led to the declaration of a pandemic. The accompanying restrictions on public life caused a change in the training routines of athletes worldwide. The present study aimed to investigate the effects of a 13-week supervised home training program on physical performance, sleep quality, and health-related quality of life in professional youth soccer players during the first COVID-19 lockdown in Germany.MethodsEight professional soccer players (age range 16–19; height:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…It may be assumed that the negative impact was seen also in all populations, but some data show the opposite. Lockdown had a positive impact on HRQoL in young healthy soccer players, which showed a significant improvement in general and mental health [ 24 ]. A recent study showed that SF-36 scores, except for mental health in CKD patients, were significantly lower than healthy individuals during the pandemic [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It may be assumed that the negative impact was seen also in all populations, but some data show the opposite. Lockdown had a positive impact on HRQoL in young healthy soccer players, which showed a significant improvement in general and mental health [ 24 ]. A recent study showed that SF-36 scores, except for mental health in CKD patients, were significantly lower than healthy individuals during the pandemic [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of the sleep quality of the athletes was investigated in four studies and significant changes were observed in the duration and quality of sleep of soccer athletes ( Facer-Childs et al, 2021 ; Han et al, 2021 ). The effects of home training during lockdown brought positive results in the sleep of athletes ( Keemss et al, 2022 ; Romdhani et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, younger athletes and those involved in individual sports often increased their sporting activities during the lockdown, thereby improving their fitness levels compared with those who were less active or inactive [ 2 , 3 , 8 , 21 , 22 ]. Other studies indicate that older athletes (over 55 years) and team sports athletes encountered more difficulties in maintaining regular sporting activities during and after the lockdown [ 4 , 19 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…For many, sport is a fundamental aspect of life, acting as a vital link between body and mind. It not only helps sustain physical and mental well-being but also reinforces socio-communal bonds [ 1 , 2 , 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation